Software for GENESYS: The Cardiff Grammar Text-Sentence Generator. Prototype 3 - Fawcett, Robin P. (2006)
The Cardiff Grammar Generator is a computer program for the generation of English text-sentences. The current version of the generator is a Visual Basic 6.0 implementation of Cardiff Grammar Generator developed by Víctor Castel.